Implementasi Model Guided Discovery Learning Berbantuan Simulasi PhET dalam Pembelajaran Sains: Tinjauan Literatur Naratif - Baiq Nabila Saufika Zainuri; Gunawan Gunawan (Indonesian Publication Center, 2022)
This narrative review study examines the concept and implementation of the Guided Discovery Learning model assisted by PhET simulations in science education. This study was conducted using a narrative literature review method through the analysis of various relevant research articles from national and international journals. The results of the study indicate that the application of Guided Discovery Learning supported by PhET simulations can improve student learning activities, conceptual understanding, and scientific process skills. In addition, the use of PhET simulations provides opportunities for students to explore concepts virtually, thereby helping to visualize abstract scientific phenomena. The integration of the Guided Discovery Learning model and PhET simulations also has the potential to create more interactive, exploratory, and meaningful learning. Therefore, the use of this learning model can be an alternative effective learning strategy to improve the quality of science learning.